2017
DOI: 10.1039/c6ee03051c
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency photovoltaic cells with wide optical band gap polymers based on fluorinated phenylene-alkoxybenzothiadiazole

Abstract: A new series of wide band gap photovoltaic polymers based on a fluorinated phenylene-alkoxybenzothiadiazole unit with an optical band gap of over 1.90 eV are designed and utilized for high-performance single- and multi-junction bulk heterojunction polymer solar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 60 publications
1
57
0
Order By: Relevance
“…[26] Whereas previousf luorination processes have usuallyi nvolvede xpensive fluorination reagents and complicated synthetic steps, cheap fluorinated benzene derivatives can easily be obtained from commercial materials. [15,27,28] Moreover,f luorinated benzene can also enhancet he molecular planarity and extinction coefficient, as well as reduce energy levels,r elative to its non-fluorinateda nalogues. For example, Kim et al reported as eries of semicrystalline polymers containing fluorinated benzene units.…”
Section: Fluorinated Polymer Donorsmentioning
confidence: 99%
See 2 more Smart Citations
“…[26] Whereas previousf luorination processes have usuallyi nvolvede xpensive fluorination reagents and complicated synthetic steps, cheap fluorinated benzene derivatives can easily be obtained from commercial materials. [15,27,28] Moreover,f luorinated benzene can also enhancet he molecular planarity and extinction coefficient, as well as reduce energy levels,r elative to its non-fluorinateda nalogues. For example, Kim et al reported as eries of semicrystalline polymers containing fluorinated benzene units.…”
Section: Fluorinated Polymer Donorsmentioning
confidence: 99%
“…For example, Kim et al reported as eries of semicrystalline polymers containing fluorinated benzene units. [27] They found that the fluorination number and positiono nb enzene could significantly affect the molecular photophysical and optoelectronic properties, which have ac rucial impact on the device performance. In the PC 71 BM-basedO SCs,P DTBTBz-2F-containing para-difluorinated benzene showed ah igherP CE of 9.8 %b ecause of improved molecular symmetry and crystallinity.Z hang et al [28] synthesized ap olymer,P FOPB, with tetrafluorinated 2D-phenyl-BDT.…”
Section: Fluorinated Polymer Donorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five types of single‐junction devices with a device configuration of ITO/ZnO/active layer/MoO 3 /Ag were fabricated using PDTBTBz‐2F, PBTDT, PPDT2FBT, PTB7‐Th, and P2 blends with PC 71 dM. Optimal device conditions of PDTBTBz‐2F, PPDT2FBT, PTB7‐Th, P2 blends were adopted and based on previous studies from our group . In addition, the new wide‐bandgap donor polymer PBTDT was recently synthesized and optimized by our group; the synthetic details are included in the Supporting Information.…”
Section: Tm Simulationsmentioning
confidence: 99%
“…Most studies have focused on the tandem architecture, in which identical or different absorber layers are used, resulting in maximum efficiencies in the range of 10-13%. [11][12][13][14][15][16][17][18][19][20][21][22] At least conceptually, stacking three absorber layers in a triple-junction solar cell can lead to a further increase in efficiency. There are few examples of triple-junction organic solar cells.…”
mentioning
confidence: 99%